ASPEK HUKUM PERAN SERTA MASYARAKAT DALAM MEMELIHARA KELESTARIAN FUNGSI LINGKUNGAN HIDUP PADA KAWASAN PERTAMBANGAN BATUAN DI DONGGALA - M. Taufan (ISTIQRA, 2017)
This study aims to determine the form of legal aspect of community participation in maintaining the environment preservation in stone mining areas in Donggala,and comprehending consequences of the stone mining activities against the environment preservation in Donggala.This research was conducted in Donggala, Central Sulawesi. This research used socio-juridical legal research. Data were analyzed qualitatively.The result showed that the community participation in maintaining the environment preservation in stone mining areas in Donggala was conducted in various forms, namely, in the planning process, decision-making, assessment, policy development, evaluation, monitoring, and information and access to decision-making. Significant impacts arising from stone mining activities on the environment preservation, among others; geophysical, chemical, biological, and socio-cultural